1985
DOI: 10.2466/pms.1985.61.3f.1135
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Specificity of Anticipation of Coincidence

Abstract: This investigation was conducted to determine if anticipation of coincidence as measured by the Bassin timer relates to “real world” skill of ball batting and to investigate further sex differences in perceptual-motor skills. 24 varsity athletes from a Midwest university's baseball and softball teams were tested on the Bassin timer and their batting averages were obtained from their respective coaches. A nonsignificant correlation suggests that the task on the Bassin timer is different from the anticipation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
4

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 3 publications
1
19
1
4
Order By: Relevance
“…This argument holds that males are typically encouraged to develop their athletic prowess, while females are instructed to behave in a feminine manner, which often translates into an avoidance of most sports and vigorous activities. However, when women are allowed to develop their athletic skills and receive training like men, a similar performance is seen (Petrakis, 1985). Regarding the second assumption, men's greater visuospatial skill has been corroborated (Bell, Willson, Wilman, Dave, & Silverstone, 2006;Dane & Erzurumluoglu, 2003;Parsons et al, 2004;Voyer, Rodgers, & McCormick, 2004).…”
Section: Discussionmentioning
confidence: 82%
“…This argument holds that males are typically encouraged to develop their athletic prowess, while females are instructed to behave in a feminine manner, which often translates into an avoidance of most sports and vigorous activities. However, when women are allowed to develop their athletic skills and receive training like men, a similar performance is seen (Petrakis, 1985). Regarding the second assumption, men's greater visuospatial skill has been corroborated (Bell, Willson, Wilman, Dave, & Silverstone, 2006;Dane & Erzurumluoglu, 2003;Parsons et al, 2004;Voyer, Rodgers, & McCormick, 2004).…”
Section: Discussionmentioning
confidence: 82%
“…Two studies, which used the Bassin timer to look at the male advantage for CAT, failed to produce good evidence for the influence of experience. Petrakis (1985) recruited female softball players (N = 9) and male baseball players (N = 15) and found no significant sex difference in terms of accuracy. Unfortunately, this failure to find a significant sex difference is not strong evidence for the effect of experience because there was no control group of women who did not play ball games.…”
Section: Possible Origins Of the Sex Differences In Catmentioning
confidence: 98%
“…It should be kept in mind that alcoholism has several causes. Recently, evidence has suggested that some forms of alcoholism have a significant genetic basis (Cloninger, Bohman, & Sigvardsson, 1981;Goodwin 1976Goodwin , 1979Petrakis, 1985). The evidence is strongest for early onset alcohol addiction that is associated with a general disposition toward impulsive and antisocial behavior; however, it is important to stress that genes are not the only cause of alcoholism.…”
Section: Drunken Relief: Alcohol and The Allocation Of Attention To Omentioning
confidence: 99%